2001
DOI: 10.1002/jnr.1093
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for neuroprotection against L‐trans‐2,4‐pyrrolidine dicarboxylate‐induced neuronal damage during energy impairment in vitro

Abstract: Increased levels of extracellular excitatory amino acids and failure of energy metabolism are two conditions associated with brain ischemia. In the present study we have combined the simultaneous inhibition of glutamate uptake and mitochondrial electron transport chain to simulate neuronal damage associated with brain ischemia. Results show that cerebellar granule neurons are not vulnerable to transient glutamate uptake inhibition by L-trans-pyrrolidine-2,4-dicarboxylate (PDC) despite the increase in the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 63 publications
(71 reference statements)
4
35
0
3
Order By: Relevance
“…Several studies have shown a neuroprotective effect of administration of pyruvate or lactate after experimental inhibition of energy metabolism (Desagher et al, 1997;Maus et al, 1999;Schurr et al, 1999;Gramsbergen et al, 2000;Sheline et al, 2000;Garcia and Massieu, 2001). This effect has been attributed to the role of pyruvate or lactate as precursors for acetyl ϳ CoA and to the antioxidant action of pyruvate through which pyruvate is decarboxylated to acetate.…”
Section: Neuroprotective Effect Of Pyruvate Administrationmentioning
confidence: 98%
“…Several studies have shown a neuroprotective effect of administration of pyruvate or lactate after experimental inhibition of energy metabolism (Desagher et al, 1997;Maus et al, 1999;Schurr et al, 1999;Gramsbergen et al, 2000;Sheline et al, 2000;Garcia and Massieu, 2001). This effect has been attributed to the role of pyruvate or lactate as precursors for acetyl ϳ CoA and to the antioxidant action of pyruvate through which pyruvate is decarboxylated to acetate.…”
Section: Neuroprotective Effect Of Pyruvate Administrationmentioning
confidence: 98%
“…ions and the activation of NMDA receptors by ambient glutamate. Previous studies have shown that neuronal death induced by the accumulation of glutamate and aspartate after inhibition of glutamate transporters is facilitated in the striatum of animals previously treated with the mitochondrial toxin 3-NP, an irreversible inhibitor of complex II of the mitochondrial electron transport chain [219]. Similarly, inhibition of the glycolytic enzyme, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), by iodoacetate (IOA) facilitates neuronal damage induced by glutamate transport inhibition or by the intrastriatal administration of glutamate [220].…”
Section: Disease Conditions Associated With Secondary Excitotoxicitymentioning
confidence: 99%
“…In fact, exogenous administration of β-hydroxybutyrate can reduce brain damage and improve neuronal function in models of brain hypoxia, anoxia, and ischemia (Cherian et al, 1994;Dardzinski et al, 2000;Suzuki et al, 2001Suzuki et al, , 2002Smith et al, 2005). In addition, the other ketone bodies, acetoacetate and acetone, which are β-hydroxybutyrate metabolites and can also serve as alternative energy sources, have similar neuroprotective effects (Garcia and Massieu, 2001;Massieu et al, 2001Massieu et al, , 2003Noh et al, 2006). Interestingly, in rats receiving a ketogenic diet, neuronal uptake of β-hydroxybutyrate is increased after cortical impact injury in comparison with animals receiving a standard diet (Prins et al, 2004).…”
Section: Ischemia and Traumatic Brain Injurymentioning
confidence: 99%